Atypical immunologic response in a patient with CRIM-negative Pompe disease - Abbott, Mary-Alice (2011)
We report the clinical course of a patient with severe infantile onset Pompe disease [cross-reactive immunologic material (CRIM) negative, R854X/R854X] who was diagnosed prenatally and received standard dosing of alglucosidase alfa (Myozyme®) enzyme replacement therapy (ERT) from day 10 of life until she passed away at the age of 3 years 9 months. In the immediate neonatal period there was cardiomegaly on chest X-ray, cardiac hypertrophy by echocardiogram, and development of a wide complex tachycardia. CRIM negative (CN) status was suspected based on her family history, and the available data at the time indicated that CN patients had limited survival even with ERT. However, given the opportunity for very early treatment, the treating provider and family elected to initiate treatment with ERT, without immune modulation. By 9 months of age echocardiogram was normal. Early motor development was within normal limits but by 2 years of age her developmental progress had slowed. She seroconverted by the 4th month of ERT, and anti-rhGAA antibody titers peaked at 25,600 in the 27th month. Immunomodulatory therapy was considered but declined by family. She acquired Influenza A at 2 years 6 months, which led to a prolonged hospitalization with invasive respiratory support, and placement of tracheostomy and gastrostomy tube. Her developmental progress ceased, and she died suddenly at home from a presumed cardiac event at age 3 years 9 months. The poor outcomes observed in CN patients have been attributed to the development of high sustained antibody titers. Although this CN patient’s anti-rhGAA response was elevated and sustained, it is unlike any of the 3 patterns that have been previously described: high titer CN, high titer CRIM positive (HTCP), and low titer CP (LTCP) patients. This patient’s clinical course, with achievement of 24 months of motor gains, 30 months of ventilator-free survival and 45 month survival, is like that of only a fraction of ERT treated CN patients, yet it is identical to other reported CN patients in its relentless progression and early fatality. The immunologic response (moderate sustained antibody titers) described here has not been previously reported and may have played a role in the overall pattern of developmental decline. In light of proposed universal newborn screening for Pompe disease, there is an urgent need for improved understanding of the interplay between immunologic responses to the only available treatment, ERT, and the relentless nature of this disease in CN patients.